(untitled) (Chittagong University Journal of Biological Sciences, 2013)
This study was designed to find out the anxiety levels of the mothers in relation to birth status of the babies and anxiety in relation to age of the mothers. The sample consisted mothers of 25 premature born babies and mothers of 25 normal born babies. They were given by the Bengali version of Dutt Personality Inventory to answer. Data were analyzed by t-test, chi-square and product moment correlation. The results revealed that t-ratio (-3.101, df = 48, p<0.05) was significant, i.e. the mothers of premature born babies were more anxious than the mothers of normal born babies. The results also indicated that the value of chi-square (chi-square = 6.894, df = 2, p<0.05) was also significant. The significant correlation (r = -0.335 at the 0.05 level) was found between the age of mothers and the anxiety score of mothers. Nevertheless, the child status of mothers was a dominating factor or component to influence the correlation. The results manifested that significant difference was found between mothers of premature born babies and mothers of normal born babies regarding their anxiety level. Mothers of premature born babies had possessed more anxiety compare to mothers of normal born babies. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13397 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):131-140, 2009